The Effect of The Concept Map Method on The Outcome of Learning Biology of High School Students on Ecosystem Materials - Tamimi, Chairul (Islamic Journal of Integrated Science Education (IJISE), 2022)
This study aims to determine the effect of using the concept map method on the biology learning outcomes of Al-Hidayah Senior High School students in Medan, Indonesia. This research is a quantitative research with a Quasi Experiment approach (quasi-experiment). The population and sample in this study were students of class X which consisted of 2 classes totaling 50 students. The research instrument used to determine student learning outcomes is using multiple choice tests in the form of pre-test and post-test as many as 20 questions that have been validated by expert lecturers and students. The research findings showed that the average pretest score for the Experimental class was 35.00, while the control pretest had an average score of 30.00 and the posttest result for the Experimental class was 83.00, while the average for Control was 70.00. And in this study, data analysis using the Independent Sample t-test showed that sig < 0.05 with a sig value of 0.00 < 0.05 with a t-count value of 6.189 and a t-table of 2.02 concept maps so that Ho was rejected and Ha received. So it can be concluded that there is an effect of Concept Map on student learning outcomes on ecosystem material in class X SMA Al-Hidayah Medan